The short-term effects of fiscal policy in Mexico: An empirical study - Cuevas Ahumada, Víctor M. (Estudios Económicos de El Colegio de México, 2009)
This paper investigates the short-term effects of fiscal policy on the Mexican economy. The empirical evidence shows that a fiscal expansion, resulting from a reduction in public sector revenues, produces the following effects: the money supply rises together with interest rates and prices, the real exchange rate depreciates despite higher interest payments to investors, economic activity increases and the trade balance deteriorates. An interesting finding is that fiscal expansion leads to real exchange rate depreciation in spite of an upward trend in interest rates, which is broadly consistent with the so-called country risk view of fiscal policy.